Strategi Komunikasi Penyidik Kepolisian Resor Aceh Tengah Dalam Proses Interogasi Tersangka Tindak Pidana Pembakaran Rumah - Julmahdi, Julmahdi; Surya, Achmad; Harahap, Viana Safrida (Universitas Gajah Putih, 2022)
As a state law enforcement tool, the National Police plays an important and strategic role. It is important because the function of law enforcement is usually initiated by the Police as a part of other law enforcement elements, such as prosecutors and judges. The communication strategy is a series of activities which includes planning a series of activities designed with different techniques and approaches, making it easier to uncover criminal cases. Observing these problems, it is clear that the communication strategy is very urgent to be mastered by every police investigator personnel of the Central Aceh resort in uncovering a criminal act and can determine the suspect in accordance with the applicable laws and regulations. The purpose of the study was to determine the investigator's communication strategy in the interrogation process of the suspect in the crime of burning a house, and to find out what factors hindered the investigator's communication strategy in the interrogation process of the suspect in the crime of burning a house. This research is a type of qualitative descriptive research, namely research that has descriptive results in the form of words and writings from informants studied by researchers, while the approach used in this study is a descriptive approach where researchers look for facts, phenomena about the communication strategy of district resort police investigators. Aceh is in the process of interrogating a suspect in the crime of burning a house. Sources of data used are primary data obtained directly in the field and secondary data obtained from literature or library materials. The results of the study show that the communication strategy used by investigators in the interrogation process of the suspect in the crime of burning a house is in accordance with the SOP that has been set, and the interrogation communication strategy used is persuasive communication and interpersonal communication. Persuasive communication is carried out using clear, firm and straightforward language. In addition to persuasive communication techniques, interpersonal communication techniques are also an option for investigators when interrogating suspects, because they treat suspects humanely by respecting their human values. The inhibiting factor of the investigator's communication strategy in the interrogation process of the suspect in the crime of burning a house, the information from the suspect which is always different, even seems to be changing and answering questions from investigators is often convoluted and the suspect does not want to answer questions from investigators, making it difficult for investigators to obtain information from investigators. suspect or perpetrator of a crime.